Chromatic Gradient Is a Figuration Characteristic in Bin Khfaja AL-Andalusy Poem - Mohammed, Saleh W. (Humanities Journal of University of Zakho, 2013)
Colour hierarchy represents a forming feature and one of the nature courses features . The light intensity differs gradually in sunset times between the brilliance light of the day and its darkness. It is considered a descriptive accurate technical feature in which the artist forms a communication among the parts of his image and transfers from a part to another to achieve aesthetic and material values contributing to create visual rest in transferring among the image parts . In addition, the mental rest is achieved when the colour image matter is words for transferring among the oppositions – with its aesthetic and technical value – leads to create a fictional bar among the opposed coulors .Thus , the colour hierarchy is considered a developed movement technically and a distinct technical expressive tool . It is a technical and aesthetic element. The colour hierarchy is characterized by descriptive efficacy and its visual cognitive value that reflects the direct treatment with colours whether from the sensory visual part in the forming image or the mental part in the images that are formed mentally from the linguistic vocabularies . In addition, the colour hierarchy is considered an essential standard in the colour mixing operation , colour movement and transference in the image.